The Level of Green Behaviour, Green Knowledge, Self Esteem and Wellbeing among School Teachers in Malaysia - Norsuriani Samsudin; Balakrishnan A/L Parasuraman; Nurul Hafizah Mohd Yasin; Lee Wan Zhen (Civiliza Publishing, 2026)
The increasing emphasis on environmental sustainability in Malaysia highlights the need to assess green behaviour, green knowledge, self-esteem and well-being among school teachers, as they play a crucial role in shaping students' environmental awareness. Despite growing awareness of green practices in the education sector, limited research has explored the about teachers’ environmental behaviour, green knowledge, self-esteem and psychological well-being. This article presented a questionnaire designed to evaluate the level of green behaviour, green knowledge, self-esteem and well-being among school teachers in Malaysia and assess the reliability of the measurement instrument used. A quantitative approach was employed, and a structured questionnaire was distributed to 30 Malaysian school teachers. A pilot study was conducted, and reliability testing was measured by using Cronbach's alpha. This questionnaire consisting of 43 items was developed, demonstrating high internal consistency. The Cronbach’s alpha values for the green behaviour scales which includes individual practices, influencing others and organizational support were 0.928, 0.927 and 0.923, respectively, indicating excellent reliability. Additionally, the green knowledge, self-esteem and well-being scale yielded a Cronbach’s alpha value more than 0.9, signifying excellent reliability of the instrument. This questionnaire was found to be a viable instrument with high internal consistency to meet the study’s objectives. This study underscores the importance of integrating sustainability education with teacher well-being programs to enhance their engagement in green initiatives. Future research should explore longitudinal studies and broader demographic samples to further validate these findings and support the development of effective environmental policies in the Malaysian education sector.